수술 후 발생한 신경인성 방광 환자에 대한 치험 1례 - 박형진(Hyoung Jin Park); 심하나(Ha Na Shim); 김유경(Yu Kyung Kim); 안기영(Ki Young An); 김상우(Sang Woo Kim); 송봉근(Bong Keun Song) (동의생리병리학회지, 2005)
We treated a 51 year-old female patient of neurogenic bladder. The patient complained of urinary incontinence, lack of urine sense, loss of right leg sense etc. The symptoms developed right after spinal stenosis surgery. The symptoms didn't show any improvement continually. But after admission and treatment in our hospital, symptoms were improved from severe to mild and the score of Assesment of Bladder function got better. We continued to prescribe the herbal medicine over 8 weeks and could observe that symptoms were improved. This result suggests that oriental medical therapy is useful enough to treat the neurogenic bladder. Therefore further study of the approach and application of this treatment for neurogenic bladder would be necessary.